UMPSA produces 35 pioneer graduates of Bachelor of Automotive Technology - Nor Salwana, Mohammad Idris (UMPSA, 2023)
GAMBANG, 21 October 2023 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) made history by celebrating, for the first time, the graduates of the first batch of the Bachelor of Automotive Technology at the 18th Convocation Ceremony of UMPSA recently.